M11 Systemic Delivery Of P42 Peptide To Fight Huntington's Disease. (17th September 2014) - Bonneaud, N; Paucard, A; Bauer, C; Marelli, C; Larroque, C; Maurel, P; Maschat, F
Abstract : Background: The starting point of our study was the observation that the ratio between wild-type and mutant polyQ-Htt is crucial in Huntington's disease progression. Screening on polyQ-hHtt aggregation allowed the identification of a protective 23aa peptide (P42) lying within human Htt. Aims: The aim was to test the protective properties of P42 on different HD models: HeLa cells, Drosophila, but also R6/2 mice. Methods/techniques: The use of P42 at therapeutic ends in a mammalian model, required that this peptide was able to cross the blood-brain-barrier, and that we find a non-invasive route for chronic administration of P42. To this end, we associated two complementary strategies: i) we fused P42 to the protein transduction domain TAT to ensure its diffusion; ii) we adapted a nanostructure-based drug delivery system for brain targeting called Aonys®, where P42-TAT was formulated in a water-in-oil micro-emulsion (NP42T) and administered through buccal and/or rectal mucosa. In order to verify the pertinence of this way of administration, we also used an original imaging analysis of P42 derivatives, using MALDI Imaging Mass Spectrometry on brain sections. Results/outcome: - We first verified that the fusion P42-TAT peptide did not change the functionality of P42, and identified a dose-response effect of P42-TAT action in HeLa cells. - To investigate the therapeutic potential of NP42T, buccal and rectal administrations were performed daily in R6/2 HD mouse model. The effects of NP42T treatment were analysed on a range of behavioural associated defects (foot-clasping, rotarod or body weights), and several markers (aggregation, astrogliosis or ventricle areas) recorded on brain sections. Conclusion: Our data globally identify an efficient protective effect of the NP42T, leading to a clear recovery of all the phenotypes tested. This study not only shows that we identified an efficient peptide against HD, but it also describes a powerful delivery technology.